Analysis of Critical Thinking, Creative Thinking and Problem Solving Skills on Elementary School Students: A Descriptive Correlation Study - Amrina, Zulfa; Alfino, Joni; Sari, Syafni Gustina; Hahsa, Nurham (FKIP Universitas Lampung, 2024)
The 21st-century competencies have become a primary focus for enhancing human resource capacity in Indonesia. The 21st-century competencies refer to a set of skills necessary for development in the modern era. These competencies include creative thinking, critical thinking and problem solving, communication, and collaboration, collectively known as the 4C skills. The 4C skills of students in Indonesia tend to be low. Based on the observations and interviews conducted by the author with teachers and students in several schools in Padang City, it was found that the majority of students did not achieve mastery in mathematics learning. They struggled to solve the mathematical problems presented to them. This research aims to analyze the relationship between critical and creative thinking skills toward problem-solving abilities of elementary school students in Padang City. This is correlational descriptive research. The study was conducted on fifth-grade students at SD 22 Kampung Dalam Padang. A random sample of 127 students was taken. The instruments used included a questionnaire for critical thinking skills, a questionnaire for creative thinking skills, and an essay test on problem-solving abilities. Data were analyzed descriptively, quantitatively, and inferentially. The results of the data analysis indicated that there was a significant relationship between critical and creative thinking skills toward students' problem-solving abilities. Keywords: critical, creative and problem-solving skill, mathematics.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp784-791